2023
DOI: 10.3390/risks11020028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Family Control on Earnings Management: The Role of Leverage

Abstract: This study aims to examine whether family control has a positive effect on earnings management of manufacturing companies and whether leverage weakens the positive effect of family control on earnings management. This study uses panel data for the 2015–2019 observation year. The research population consists of companies listed on the Indonesian capital market. Sample selection was performed with a purposive sampling approach using certain criteria, namely: the company was not delisted during the observation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
2
0
0
Order By: Relevance
“…This implies that family ownership exerts a lowering effect on the CEO's financial expertise ability to stem earnings management. This finding is consistent with Murni et al . (2023) and Kumala and Siregar (2021) who claim that family control has a positive effect on earnings management in Indonesia.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This implies that family ownership exerts a lowering effect on the CEO's financial expertise ability to stem earnings management. This finding is consistent with Murni et al . (2023) and Kumala and Siregar (2021) who claim that family control has a positive effect on earnings management in Indonesia.…”
Section: Resultssupporting
confidence: 94%
“…This implies that family ownership exerts a lowering effect on the CEO's financial expertise ability to stem earnings management. This finding is consistent with Murni et al (2023) and Kumala and Siregar (2021) who claim that family control has a positive effect on earnings management in Indonesia. Nonetheless, they contradict with the findings of Richardson and Leung (2011) who reported that family firms are less prone to the practices of earnings management than non-family firms in Hong Kong.…”
Section: Multivariate Analysissupporting
confidence: 91%
“…Our investigation confirms that leverage positively affects accruals-based earnings management (Hoang & Phung, 2019;Murni et al, 2023;Tonye & Sokiri, 2020). Our analysis also shows how business risk affects this relationship.…”
Section: The Influence Of Cash Flows Volatility On the Relationship B...supporting
confidence: 80%
“…As most obligations increase, accruals earnings management decreases. Financial leverage and accruals earnings management were positively correlated in Egyptian enterprises by Bassiouny (2016), Kalbuana et al ( 2021) and Murni et al (2023). Jordanian and Tunisian enterprises have a favorable relation among accruals earnings management and leverage, according to Abbadi et al (2016) and Lanouar et al (2013).…”
Section: Literature Review 3 Earnings Management and Leveragementioning
confidence: 93%